A T-shaped 1 × 8 balanced optical power splitter based on 90° bend asymmetric vertical slot waveguides. (12th March 2019) - Butt, M A; Khonina, S N; Kazanskiy, N L
Abstract: We proposed a T-shaped 1 × 8 balanced optical power splitter (OPS) design. The working principle of the OPS is based on the coupled-mode theory. Vertical silicon slot waveguides are utilized in the design, which offers optical confinement in transverse electric-polarization. The layout of the OPS is distinctive and provides four output ports, with each on two sides of the chip. Moreover, the bending losses of the waveguides are reduced by 80% by shifting the slot towards the outer periphery of the bend compared to the symmetric slot waveguide. Numerical investigations suggested that this device can work across the whole C-band, with a maximum of 43% power decay.